Association of early donor chimerism status with survival outcomes in post allogeneic hematopoietic stem cell transplant patients of nonmalignant diseases - Sial, Nadia; Ahmed, Parvez; Feroza Hamid Wattoo; Ali, Nadir (Journal of the Pakistan Medical Association, 2021)
Objective: To highlight the association of early donor chimerism status at 2nd month with various survival outcomes. Method: The retrospective study was conducted at the Armed Forces Bone Marrow Transplant Centre, Rawalpindi, Pakistan, and comprised patient data from January 2011 to July 2016. Data related to participants who underwent human leukocyte antigen-matched transplants for bone marrow failure syndrome and beta thalassemia major. Short tandem repeat-based polymerase chain reaction was used to assess donor chimerism status. Overall survival, disease-free survival, relapse-free survival, and graft versus host disease-free survival rates were noted. Data was analysed using SPSS 23. Results: Of the 106, 64(60.4%) had bone marrow failure syndrome and 42(39.6%) had beta thalassemia major. The overall median follow-up was 13.53 months (range: 1.81-62.73 months). Early donor chimerism status was associated with overall survival (p=0.02) and disease-free survival (p=0.01). Mixed donor chimerism was less hazardous in terms of overall survival (p=0.04) and disease-free survival (p=0.02). Conclusion: Early mixed donor chimerism contributed to optimal survival in nonmalignant disease. Key Words: Hematopoietic stem cell transplantation, Nonmalignant diseases, Survival outcome, Conditioning regimen.